BRAC-Global Resource Mobilization and Partnership’s Silatech project impact on young entrepreneurs' financial Inclusion & skill development - Aurthi, Mahjabin Tishan (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.